In situ strength profiles along two adjacent vertical drillholes from digitalization of hydraulic rotary drilling - Xuefan Wang; Peng Peng; Zhigang Shan; Zhongqi Yue (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
Drilling speed and associated analyses from factual field data of hydraulic rotary drilling have not been fully utilized. The paper provides the reference and comparison for the utilization of drilling information from two adjacent vertical drillholes that were formed with the same hydraulic rotary drilling machine and bit. The analysis of original factual data is presented to obtain the constant drilling speed during net drilling process. According to the factual data along two adjacent drillholes, the digitalization results respectively include 461 linear zones and 210 linear zones with their constant drilling speeds and associated drilling parameters. The digitalization results can accurately present the spatial distributions and interface boundaries of drilled geomaterials and the results are consistent with the paralleled site loggings. The weighted average drilling speeds from 2.335 m/min to 0.044 m/min represent 13 types of drilled geomaterials from soils to hard rocks. The quantitative relation between drilling speed and strength property is provided. The digitalization results can statistically profile the basic strength quality grades of III to VI from soils to hard rocks. The thickness distributions of four strength quality grades are presented for each individual type of geomaterials along two drillholes. In total, 50.2% of geomaterials from drillhole A are grade IV and 57.4% of geomaterials from drillhole B are grade III. The digitalization results can offer an accurate and cost-effective tool to quantitatively describe the spatial distribution and in situ strength profile of drilled geomaterials in the current drilling projects.